Effect of the defected microstrip structure shapes on the performance of dual-band bandpass filter for wireless communications - Mussa Mabrok; Zahriladha Zakaria; Yully Erwanti Masrukin; Tole Sutikno; Hussein Alsariera (Institute of Advanced Engineering and Science, 2021)
Due to the progression growth of multiservice wireless communication systems in a single device, multiband bandpass filter has attract a great attention to the end user. Therefore, multiband bandpass filter is a crucial component in the multiband transceivers systems which can support multiple services in one device. This paper presents a design of dual-band bandpass filter at 2.4 GHz and 3.5 GHz for WLAN and WiMAX applications. Firstly, the wideband bandpass filter is designed at a center frequency of 3 GHz based on quarter-wavelength short circuited stub. Three types of defected microstrip structure (DMS) are implemented to produce a wide notch band, which are T-inversed shape, C-shape, and U-shape. Based on the performance comparisons, U-shaped DMS is selected to be integrated with the bandpass filter. The designed filter achieved two passbands centered at 2.51 GHz and 3.59 GHz with 3 dB bandwidth of 15.94% and 15.86%. The proposed design is very useful for wireless communication systems and its applications such as WLAN and WiMAX.